The Implementation of Collaborative Governance in the Wethan Wonderland Tourism Program in Surabaya - Dieo Oktavian Armano; Arya Nur Indra Kusuma Herdianto; Achmad Firza Rahmadani; Berliana Mustika Rani (Universitas Negeri Gorontalo, 2026)
Community-based tourism is a destination development strategy that supports improvements in community well-being and regional development. Wethan Wonderland Surabaya is a community-based tourism destination developed through collaboration between the government, the community, and the private sector. This study aims to analyze the implementation of collaborative governance in the Wethan Wonderland Surabaya Tourism Program using the theory of Ansell and Gash (2008). The study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The results indicate that collaborative governance has been implemented across four dimensions: starting conditions, institutional design, facilitative leadership, and collaborative process. Collaboration among stakeholders has fostered community participation, tourism development, environmental improvement, and local economic growth through SMEs and educational tourism. However, the development of Wethan Wonderland still faces challenges, including limited infrastructure, transportation accessibility, and suboptimal digital information integration. This study demonstrates that stakeholder synergy, facilitative leadership, and sustained communication and coordination are critical factors in supporting the sustainability of the tourism destination.